Development of Guided Inquiry-Based LKS on the Concept of Borax to Develop Students' Food Safety Knowledge and Skills - Evita, Wiwik; Kurnia, Nova; Khaeruma, Khaeruma; Nurhazlinda, Nurhazlinda (Reflection Journal, 2024)
The misuse of borax in food is a critical issue due to its significant health risks. This research aimed to develop guided inquiry-based student worksheets (LKS) on the concept of borax to enhance students' knowledge and skills in food safety. The study employed the 4-D development model, which includes defining, designing, developing, and disseminating stages. Conducted with 30 eighth-grade students at SMPI Sabilal Muhtadin NW Lopok, the research utilized validation sheets, questionnaires, knowledge tests, observation sheets, and documentation for data collection. Validation results indicated that the developed LKS is highly feasible with a 92.5% feasibility score. Teachers and students provided positive feedback, rating the LKS as highly feasible in material quality, presentation, and attractiveness. The knowledge test scores averaged 81.97, indicating a significant improvement in students' understanding of food safety. Additionally, the skills assessment showed an average score of 85.2, categorizing students as highly skilled in food safety practices. The findings demonstrate that the guided inquiry-based LKS effectively enhances students' food safety knowledge and skills. However, the study highlights the need for individualized learning approaches to address varying student abilities. The research concludes that innovative teaching tools like guided inquiry-based LKS are effective in improving educational outcomes. Recommendations include further development and use of such LKS in other subjects to provide meaningful and engaging learning experiences. Future research should consider broader participant demographics to enhance generalizability.